Discovery of socio-technical requirements for the design of a digital educational game - Haddad, Flávia Belintani Blum; Dias, Luiz Miguel Naldi; Corrêa, Cléber Gimenez; Peres, Letícia Mara (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: The use of digital games in several areas is a reality, getting the attention and engagement of users or players, making possible the combination of games and education, contributing to the teaching and learning process, especially in subjects that require practical activities. Problem: However, to build interactive games it is essential to know the social context that will be inserted through the proper use of educational approaches and Software Engineering. Solution: This paper presents the application of concepts, techniques, tools, and artifacts proposed by Socially Aware Design to discover the socio-technical requirements used in the construction of a digital educational game for the teaching of Software Engineering subjects. IS Theory: This work considers design theory regarding the artifacts that contribute to the construction of IS. Method: Semi-participatory design workshops were held for the characterization of the problem, solution proposals, and requirements elicitation, generating the stakeholder diagram, the value prospecting framework, the evaluation framework, the semiotic ladder, and a prototype of the game used during the design process. Summary of results: The artifacts generated contributed to the number of stakeholders who participated in the workshops and, consequently, to the discovery of socio-technical requirements, enabling a greater understanding of the problem and improvements in the design of the solution. Contributions and Impact in the IS area: The relevance of this work lies in the use, improvement, and dissemination of Socially Aware Design to build more humanized, sustainable, and inclusive interactive systems.